Noise! noise! noise! - Sommer, Carl, 1930-; James, Kennon (Houston, TX : Advance Pub., 2003)
Two mice are unhappy with living in the forest, until they move to a farmhouse and discover how good things had been before.
"Fun times with tolerance/friendship/appreciation"--Cover.
"Grades K-3"--Dust jacket flap.
Keywords: Mice -- Juvenile fiction; Animals -- Juvenile fiction; Contentment -- Juvenile fiction; Mice -- Fiction; Animals -- Fiction; Contentment -- Fiction